Role of Bispecific Antibodies in Relapsed/Refractory Diffuse Large B-Cell Lymphoma in the CART Era - González Barca, Eva (Frontiers in Immunology, 2022)
Diffuse large B-cell lymphoma is an aggressive and biologically heterogeneous disease. R-CHOP is the standard first line therapy and cures more than 60% of patients. Salvage high-dose chemotherapy with autologous stem cell transplant remains the standard second-line treatment for relapsed or refractory patients, and recently, three CD19 chimeric antigen receptor T cells (CART) cell products have been approved beyond 2 prior lines of systemic therapy. Nevertheless, some patients are not eligible for transplant or CARTs, or progress after these treatments. In this context, IgG-like bispecific antibodies (BsAbs) have been designed to treat B‐cell lymphomas. They combine two different monospecific antigen‐binding regions that target CD20 on B cells and engage T cells via CD3 in a 1:1 or 2:1 CD20:CD3 antigen binding fragment (Fab) format. The results of different phase 1 trials with BsAbs, including mosunetuzumab, glofitamab, epcoritamab and odeonextamab, have been recently published. They are infused intravenously or subcutaneously, and have a favorable toxicity profile, with reduced cytokine release syndrome and neurotoxicity. Moreover, these BsAbs have demonstrated very promising efficacy in B-cell lymphomas, including in aggressive lymphomas. New trials are currently ongoing to confirm BsAbs efficacy and tolerability, as well as to explore its efficacy in different lines of therapy or in combination with other drugs.